Striatal phosphodiesterase 10A availability is altered secondary to chronic changes in dopamine neurotransmission - Maarten Ooms; Sofie Celen; Ronald De Hoogt; Ilse Lenaerts; Johnny Liebregts; Greet Vanhoof; Xavier Langlois; Andrey Postnov; Michel Koole; Alfons Verbruggen; Koen Van Laere; Guy Bormans (SpringerOpen, 2016)
Abstract Background Phosphodiesterase 10A (PDE10A) is an important regulator of nigrostriatal dopamine (DA) neurotransmission. However, little is known on the effect of alterations in DA neurotransmission on PDE10A availability. Here, we used [18F]JNJ42259152 PET to measure changes in PDE10A availability, secondary to pharmacological alterations in DA release and to investigate whether these are D1- or D2-receptor driven. Results Acute treatment of rats using D-amphetamine (5 mg, s.c. and 1 mg/kg i.v.) did not result in a significant change in PDE10A BPND compared to baseline conditions. 5-day D-amphetamine treatment (5 mg/kg, s.c.) increased striatal PDE10A BPND compared to the baseline (+24 %, p = 0.03). Treatment with the selective D2 antagonist SCH23390 (1 mg/kg) and D-amphetamine decreased PDE10A binding (-22 %, p = 0.03). Treatment with only SCH23390 further decreased PDE10A binding (-26 %, p = 0.03). No significant alterations in PDE10A mRNA levels were observed. Conclusions Repeated D-amphetamine treatment significantly increased PDE10A binding, which is not observed upon selective D1 receptor blocking. This study suggests a potential pharmacological interaction between PDE10A enzymes and drugs modifying DA neurotransmission. Therefore, PDE10A binding in patients with neuropsychiatric disorders might be modulated by chronic DA-related treatment.